OARSI Clinical Trials Recommendations: Knee imaging in clinical trials in osteoarthritis. Issue 5 (May 2015) - Hunter, D.J.; Altman, R.D.; Cicuttini, F.; Crema, M.D.; Duryea, J.; Eckstein, F.; Guermazi, A.; Kijowski, R.; Link, T.M.; Martel-Pelletier, J.; Miller, C.G.; Mosher, T.J.; et al.
Summary: Significant advances have occurred in our understanding of the pathogenesis of knee osteoarthritis (OA) and some recent trials have demonstrated the potential for modification of the disease course. The purpose of this expert opinion, consensus driven exercise is to provide detail on how one might use and apply knee imaging in knee OA trials. It includes information on acquisition methods/techniques (including guidance on positioning for radiography, sequence/protocol recommendations/hardware for magnetic resonance imaging (MRI)); commonly encountered problems (including positioning, hardware and coil failures, sequences artifacts); quality assurance (QA)/control procedures; measurement methods; measurement performance (reliability, responsiveness, validity); recommendations for trials; and research recommendations.